Interbed patterns division and its effect on production performance for class I hydrate deposit with mudstone interbed. (15th November 2020) - Bai, Yajie; Hou, Jian; Liu, Yongge; Lu, Nu; Zhao, Ermeng; Ji, Yunkai
Abstract: Mudstone is widely existed in sandstone hydrate deposits, so it is necessary to discuss regularization of mudstone interbeds in hydrate development. To provide guidance for the site selection of production wells, adjustment of development scheme and prediction of productivity prediction, the criteria for dividing mudstone interbed patterns was established based on the size (area factor) and location (relationship with well location). And the index describing the influence of interbed pattern was put forward: sealing degree(SD). The Class Ⅰ hydrate deposit model with interbed was established by numerical simulation method. The production characteristics of Class Ⅰ hydrate deposits with whole interbed are revealed. The production and decomposition dynamics of Class Ⅰ hydrates with different patterns of interbeds are compared, and the influence mechanism of mudstone interbeds on the production of hydrate deposits was analyzed. The cumulative gas production of hydrate can be reduced by 10% (the corresponding sealing degree(SD) is about 90%) when the mudstone interbed is whole interbed. Moreover, the gas production rate curve shows the abnormal bulge and the hydrate decomposition curve shows double peak characteristics in the whole interbed model. The influence is weak when the mudstone interbed area is less than half of the deposit area, so the shape of production performance curve remains unchanged; while the shape of hydrate decomposition curve changes when the mudstone interbed area is larger than half of the deposit area. The location of the interbed as little influence on production performance, and the closer to the well, the better for the development. For hydrate deposits with single mudstone interbed, the central position of mudstone interbed should be selected as the well position in order to avoid the inhibiting effect on depressurization development. Highlights: A criteria for dividing the mudstone interbed patterns is established. The index describing the effect of interbed pattern was put forward: sealing degree. The production performance of Class Ⅰ hydrates with whole interbed are revealed. The production dynamics of Class Ⅰ hydrates in each interbed pattern are compared. The well location of Class Ⅰ hydrates with mudstone interbeds has been selected.